A study of variations of sacral hiatus of dry human sacra in north interior Karnataka region - Vijaykumar Shinde; P S Bhusaraddi (Wolters Kluwer Medknow Publications, 2014)
Background and aims: The shape of sacral hiatus is known to show a number of anatomical variations. The shape and extent of sacral hiatus is important because in caudal epidural anaesthesia, the approach is made through sacral hiatus. The detailed anatomical knowledge of variations of sacral hiatus is very helpful to the anaesthetists to increase the success rate of caudal anaesthesia. The present study is an attempt to find out variations of sacral hiatus in north interior Karnataka region. Materials and methods: For the present study, one hundred dry human sacra obtained from north interior Karnataka region were used. Results: The inverted U shaped sacral hiatus was most common (56%). Inverted V shaped sacral hiatus was found in 24% of sacra. The other variations like irregular shaped hiatus (10%), bifid hiatus (2%), dumbbell shaped hiatus (5%), complete spina bifida (1%) and absent hiatus (2%) were also found. Conclusion: Abnormal shapes of sacral hiatus like irregular, bifid, dumbbell, completespina bifida and absent hiatus were seen in 20% of total 100 sacra belonging to north interior Karnataka.